Kesejahteraan Agama dalam Kalangan Bekas Pengguna Dadah (BPD) bagi Mengurangkan Risiko Pengulangan Dadah (Jurnal Pembangunan Sosial, 2017)
Religious is an important protective and preventive factor to help overcome social problems, particularly with regards to addiction relapse. Religion refers to a social institution which includes believers, faith and belief systems, and religious practices. Religious beliefs influence the well-being of individual and positively related to self-esteem and feeling of mastery which, in turn, are associated with psysical and psychological well-being. Religiousity is consistently linked to a positive vertical relationship between God and religion. A cross sectional quantitative research were carried out among 290 former drug users in seven Cure and Care Service Centers (CCSC) to investigate the effects of religiosity well-being on risk of drug relapse. Data were gathered using a survey questionnaire which was adapted from the Spiritual Wellbeing Scale (SWB) and Drug Taking Confidence Questionnaires (DTCQ), and was translated into the Malay language using back translation. Results revealed that there was a negative relationship between Religious Well-being (RWB) and drug relapse, in which the higher the RWB, the lower the risk of drug relapse. Thus, religious well-being approach was recommended. This approach provide an inclusive social work based interventions aimed to enhance the individual’s religious well-being through religious understanding, beliefs, and good practices towards better self-awareness, self-efficacy, resiliency, coping and self-locus control among the former drug users in order to reduce the risk of relapse.